Tecnologias na produção de mudas de romãzeiras (Punica granatum L.) - Almeida, João Paulo Nobre de (2017)
Information about seedlings formation and initial growth of the pomegranate (Punica granatum L.) is scarce in the northeastern semiarid conditions. Because of this, three experiments were carried out with pomegranates, aiming to determine the appropriate procedures for the production of seedlings with good quality and to verify its ability to adapt to the abiotic stresses in semi-arid conditions. The experiments were conducted at the Federal Rural University of the Semi-Arid (UFERSA, Mossoró Campus - RN). In the first experiment the objective was to evaluate a dormancy overrun, an emergence and an initial growth of pomegranate seedlings after different pre-germination treatments in the seeds. The treatments applied in the seeds were: control (removal of the sarcotesta); Soaking the seeds in distilled water for 24, 48, 72 and 96 hrs; immersion of the seeds in sodium hypochlorite (NaClO) for 5, 10, 15 and 20 min; immersion in gibberellic acid (GA3) at the concentrations of 250, 500 and 1000 mg L-1; immersion in concentrated sulfuric acid (H2 SO4) for 5, 10, 15 and 20 min; Immersion in hot water at 80 °C for 2, 4, 6 and 8 min, totaling 20 treatments, arranged in a randomized complete block design with 4 replications of 25 seeds, a total of 80 plots. The soaking of the seeds in water for 72 and / or 96 hours and immersion in gibberellic acid were effective in breaking dormancy of pomegranate seed. In the second experiment the adaptation and the physiological performance in pomegranate seedlings were evaluated as a function of the doses of water-retaining polymer at different levels of shading. A randomized block design was used in a 3x2 factorial scheme, with three hydrogel concentrations (0, 1 and 2 g kg-1) and two levels of shading (full sun exposure and 50% attenuation of solar radiation) and four replications. There was no influence of the use of the hydrorentering polymer on growth and dry biomass in pomegranate seedlings as a function of their growing environment. The seedlings showed better growth parameters and dry mass allocation when shaded. In the third experiment, the objective was to study the effects of salinity levels of water used on irrigation on the growth, physiology, biochemistry and tolerance of the pomegranate seedlings to the salinity. A randomized block design with five treatments (CEa of 0.6; 3.0; 6.0; 9.0; 12.0 dS m-1) and five replications was used. The salinities of irrigation water up to EC 6.0 dS m-1 did not influence the quality of pomegranate seedlings, presenting planting suitable for planting. Taking into account the criterion of evaluation of tolerance to salinity, the pomegranate seedlings in the semi-arid conditions were resilient to the salinity effects until the EC of 6.0 dS m-1. In the condition of saline stress, the pomegranate exhibits adaptive tolerance with its photosynthetic activity and elevates the accumulation of proline and soluble sugars in its leaves in the semi-arid conditions